Linking the Planetary Health Diet Index to sarcopenia: the mediating effect of the non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio (NHHR) - Chen, Huan; Wang, Zhao; Lee, Changsin; Liu, Rongcan; Song, Junlong; Zhang, Junsheng; Du, Ning; Kang, Chan (Frontiers in Nutrition, 2025)
BackgroundThe Planetary Health Diet Index (PHDI), which promotes plant-based food consumption and limits red meat and processed food intake, aligns with goals for human health and environmental sustainability. Sarcopenia, characterized by progressive muscle loss, has been increasingly associated with dietary and metabolic factors. This study aims to explore the relationship between PHDI and sarcopenia and investigates the potential mediating role of the non-high-density lipoprotein to high-density lipoprotein cholesterol ratio (NHHR).MethodsA total of 9,094 individuals from the National Health and Nutrition Examination Survey (NHANES), conducted between 2011 and 2018, were included in this analysis. Multivariable logistic regression, smooth curve fitting, and subgroup analyses were applied to explore the association between the PHDI and the likelihood of sarcopenia. Additionally, mediation analysis was performed to assess the potential mediating role of NHHR.ResultsThe findings indicated a notable negative association between PHDI and sarcopenia. After adjusting for confounding factors, a 10-unit increase in PHDI was associated with an 14% lower likelihood of sarcopenia [Odds Ratio (OR) = 0.86, 95% Confidence Interval (CI): 0.79, 0.94]. Participants in the highest PHDI tertile (T3) were observed to have a 38% reduced likelihood of sarcopenia compared to those in the lowest tertile (T1) [OR = 0.62, 95% CI: 0.43, 0.90]. Analysis of the dose–response curve suggested a linear relationship between PHDI and sarcopenia. Furthermore, a significant positive association was identified between NHHR and sarcopenia [OR = 1.09, 95% CI: 1.03, 1.16], with NHHR found to decrease as PHDI increased [beta coefficient (β) = −0.09, 95% CI: −0.11, −0.06]. Mediation analysis revealed that NHHR partially mediated the relationship between PHDI and sarcopenia, accounting for 8.33% of the total effect.ConclusionThis study highlights the observed negative correlation between PHDI and sarcopenia, with NHHR acting as a partial mediator. These findings emphasize the potential importance of dietary patterns in strategies aimed at preventing sarcopenia.